Membangun Kesadaran Politik Siswa dalam Mengukuhkan Semangat Kewarganegaraan Multikultural di SMA Negeri 5 Gorontalo: Pengabdian - Mahmud, Ramli; W. Wantu, Asmun; Mawahda, Nurul; Abdullah, Moh. Wahyudin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to build students’ political awareness in strengthening the spirit of multicultural citizenship at SMA Negeri 5 Gorontalo. Through this activity, students are expected to understand the meaning of political awareness, foster an attitude of tolerance, and appreciate diversity as part of a democratic civic character. The implementation was carried out offline using a participatory-educative approach, involving 23 students of SMA Negeri 5 Gorontalo as the target participants. The activity was conducted by three lecturers and several students from the Civic Education (PPKn) Undergraduate Program, Faculty of Social Sciences, Universitas Negeri Gorontalo. The stages of the activity included preparation, implementation through socialization and interactive discussions, participatory observation, and evaluation by distributing questionnaires to assess changes in students’ attitudes and understanding of political and multicultural values. The results showed an increase in students’ understanding and political awareness, reflected in their active participation in discussions, improved ability to express opinions critically, and enhanced respect for intercultural differences.